2015
DOI: 10.1016/j.cell.2015.10.030
|View full text |Cite|
|
Sign up to set email alerts
|

MAJIN Links Telomeric DNA to the Nuclear Membrane by Exchanging Telomere Cap

Abstract: In meiosis, telomeres attach to the inner nuclear membrane (INM) and drive the chromosome movement required for homolog pairing and recombination. Here, we address the question of how telomeres are structurally adapted for the meiotic task. We identify a multi-subunit meiotic telomere-complex, TERB1/2-MAJIN, which takes over telomeric DNA from the shelterin complex in mouse germ cells. TERB1/2-MAJIN initially assembles on the INM sequestered by its putative transmembrane subunit MAJIN. In early meiosis, telome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
171
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(182 citation statements)
references
References 53 publications
9
171
1
1
Order By: Relevance
“…In recent years, several meiosis-specific structural units that mediate chromosome attachment on the telomeric end have been identified in mice, including SUN1, KASH5, TERB1/2, and MAJIN (4)(5)(6)8). Our present study suggests that Speedy A, which was previously known solely as a Cdk activator, has a structural function in the formation of the telomere complex during meiotic prophase I in mammals.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In recent years, several meiosis-specific structural units that mediate chromosome attachment on the telomeric end have been identified in mice, including SUN1, KASH5, TERB1/2, and MAJIN (4)(5)(6)8). Our present study suggests that Speedy A, which was previously known solely as a Cdk activator, has a structural function in the formation of the telomere complex during meiotic prophase I in mammals.…”
Section: Discussionsupporting
confidence: 50%
“…We further analyzed the telomeric cap exchange that takes place in pachytene-stage germ cells (5). In wild-type spermatocytes, we observed that TRF2 (telomeric repeat-binding factor 2), a shelterin protein (28,29), was disassociated from the end of the chromosome axis and formed a ring structure, indicating that cap exchange had occurred (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors affecting telomere bouquet formation mainly participate in two aspects of telomere behavior: telomere attachment to the INM and subsequent telomere movement along the INM. Many proteins have been identified that connect telomere proteins with INM proteins, such as Bouquet 1 (Bqt1), Bqt2, Bqt3, and Bqt4 in fission yeast (Schizosaccharomyces pombe) (Chikashige et al, 2006(Chikashige et al, , 2009, Nondisjunction 1 (Ndj1) in budding yeast (Saccharomyces cerevisiae) (Conrad et al, 1997;Trelles-Sticken et al, 2000), as well as Telomere repeat binding bouquet formation protein 1 (TERB1), TERB2, and membrane-anchored junction protein (MAJIN) in mouse (Mus musculus) (Shibuya et al, 2014(Shibuya et al, , 2015. These proteins tether telomeres to the INM to ensure bouquet formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the LINC-complex protein SUN 1 (ref 192022 , MAJIN (membrane-anchored junction protein) 22 , CDK2 (cyclin-dependent kinases 2) 23 and Speedy/RINGO A (rapid inducer of G2/M progression in oocytes) 24 .…”
mentioning
confidence: 99%